Image Denoising using Improved Non-Local Means Filter - Nidhi Choudhary; Ravi Jaiswal; Siddharth Srivastava (Journal of Electronic Design Engineering, 2020)
Local filters used for denoising images do not account for nonlinear structure within the image, where similarities can be shared between spatially distant pixels which are overcome by nonlocal filters by allowing for the use of self-predictions. In this method, an improved version of nonlocal denoising filtering has been presented using quaternion non coupled means filter. The proposed method has been applied to various noisy images and shows good results in terms of performance characteristics.